Implementation of Restructuring As a Step in Financing Management Problems at BANK KB Bukopin Syariah KC Surabaya - Sulfah Sahratus Syabrinah; Sri Wigati (Jurnal Nuansa : Publikasi Ilmu Manajemen dan Ekonomi Syariah, 2024)
Restructuring is a step in overcoming financing problems that arise because debtors experience difficulties in fulfilling their obligations, which is known as default. The government, through the Financial Services Authority, asks banking institutions to identify debtors and provide financing restructuring policies with the aim of providing relief to the public, especially debtors, in financing payments. This research aims to find out how restructuring is implemented as an effort to manage problematic financing at KB Bank Syariah KC Surabaya. The research method used is a descriptive qualitative approach in the nature of library research, namely by using books and literature related to this research. The results of this research are that implementing restructuring of problematic financing in banks will benefit in the form of reducing Non-Performing Finance (NPF), which will ultimately have a positive impact on the overall health of the bank. Apart from that, from an economic perspective, the Bank will receive installment payments from debtors in accordance with the restructuring agreement that has been agreed between the bank and the debtor. The success of implementing financing restructuring depends on the intention and willingness of both parties, namely the debtor and financing, to work together in resolving financing problems that arise.